(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper details how ageing is affecting to private saving and public pensions.In this way, it analyses if Life-Cycle Hypothesis is carrying out for individuals about their saving behaviours and if Pension Public Systems can make them to vary. Forthis reason, it establishes a specifically household saving comparative for Germanyand Unites States, studying also their ageing evolution and pay capacity of publicpension retirement.